AN AXIAL STIFFNESS JUDGMENT METHOD FOR LIMIT-POINT BUCKLING OF SPATIAL COMPRESSION MEMBERS - ZHOU QiCai; LI WenJun; WU QingLong; XIONG XiaoLei (Jixie qiangdu)
Limit-point,elastic or elastoplastic,flexural or flexural-torsional buckling of spatial compression members are easy to happen in engineering structures,a simple unified buckling judgment method is need for engineering applications. This paper presented an axial stiffness judgment method,which was expressed under the Eulerian description and based on the definition of compression rod stabilization. The validity and applicability of the proposed method were verified by numerical analysis of a frame model. Then,the axial stiffness values of compression members of the frame were measured and calculated by the frame buckling experiment,and the experimental results were compared with the numerical results. Studies show that the buckling of local compression members may happen before the overall buckling of bars structures,and the axial stiffness judgment method can precisely judge the buckling of spatial compression members in engineering structures.